Generation and functional characterization of MDSC-like cells. (3rd April 2017) - Heine, Annkristin; Held, Stefanie Andrea Erika; Schulte-Schrepping, Jonas; Wolff, Julia Friederike Andrea; Klee, Kathrin; Ulas, Thomas; Schmacke, Niklas Arndt; Daecke, Solveig Nora; Riethausen, Kati; Schultze, Joachim L.; Brossart, Peter
ABSTRACT: Myeloid-derived suppressor cells (MDSC) are critical in regulating immune responses by suppressing antigen presenting cells (APC) and T cells. We previously observed that incubation of peripheral blood monocytes with interleukin (IL)-10 during their differentiation to monocyte-derived dendritic cells (moDCs) results in the generation of an APC population with a CD14 + HLA-DR low phenotype (IL-10-APC) with reduced stimulatory capacity similar to human MDSC. Co-incubation experiments now revealed that the addition of IL-10-APC to moDC caused a reduction of DC-induced T-cell proliferation, of the expression of maturation markers, and of secreted cytokines and chemokines such as TNF-α, IL-6, MIP-1α and Rantes. Addition of IL-10-APC increased the immunosuppressive molecule osteoactivin and its corresponding receptor syndecan-4 on moDC. Moreover, CD14 + HLA-DR low MDSC isolated from healthy donors expressed high levels of osteoactivin, which was even further upregulated by the auxiliary addition of IL-10. Using transcriptome analysis, we identified a set of molecules and pathways mediating these effects. In addition, we found that IL-10-APC as well as human isolated MDSC expressed higher levels of programmed death (PD)-1, PD-ligand-1 (PD-L1), glucocorticoid-induced-tumor-necrosis-factor-receptor-related-protein (GITR) and GITR-ligand. Inhibition of osteoactivin, syndecan-4, PD-1 or PD-L1 on MDSC by using blocking antibodies restored the stimulatory capacity of DC in co-incubation experiments. Activation of MDSC with Dectin-1 ligand curdlan reduced the expression of osteoactivin and PD-L1. Our results demonstrate that osteoactivin/syndecan-4 and PD-/PD-L1 are key molecules that are profoundly involved in the inhibitory effects of MDSC on DC function and might be promising tools for clinical application.